2018
DOI: 10.1101/440438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gradient in cytoplasmic pressure in the germline cells controls overlying epithelial cell morphogenesis

Abstract: It is unknown how growth in one tissue impacts morphogenesis in a neighboring tissue. To address this, we used the Drosophila ovarian follicle, where a cluster of 15 nurse cells and a posteriorly located oocyte are surrounded by a layer of epithelial cells. It is known that as the nurse cells grow, the overlying epithelial cells flatten in a wave that begins in the anterior. Here, we demonstrate that an anterior to posterior gradient of decreasing cytoplasmic pressure is present across the nurse cells and that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 97 publications
2
13
0
Order By: Relevance
“…2F). By also accounting for natural cell-to-cell variability in effective cell surface tension (34), the proposed model successfully captures experimentally observed complex transport patterns along the 16-cell tree. For example, our data show the L4 NC transiently increasing in size during NC dumping, which can occur if the L3 cell to which it is connected shrinks sufficiently such that it becomes smaller than the L4 cell.…”
Section: Resultsmentioning
confidence: 88%
“…2F). By also accounting for natural cell-to-cell variability in effective cell surface tension (34), the proposed model successfully captures experimentally observed complex transport patterns along the 16-cell tree. For example, our data show the L4 NC transiently increasing in size during NC dumping, which can occur if the L3 cell to which it is connected shrinks sufficiently such that it becomes smaller than the L4 cell.…”
Section: Resultsmentioning
confidence: 88%
“…In spite of these simplifications our theory bring several generic, robust and experimentally testable predictions. In particular, we expect our theory to be relevant, beyond lumenogenesis, to describe the hydraulic cell coarsening phenomena underlying Drosophila and C. elegans oogenesis (35,37,38). Our theory demonstrates that lumen coarsening exhibits a generic dynamic scaling behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Such important topological differences may explain why baso-lateral cavities, in contrast to their apical counterparts, appear systematically pressurized, as they need to grow against adhesive contacts; it may also explain why tissues with multiple apical lumens may fail to spontaneously resolve into a single cavity (33). Hydraulic and osmotic flows are more and more recog- nized as essential determinants of embryo and tissue shaping (8,32,(34)(35)(36)(37)(38). However only a few physical models describe the interplay between cell mechanics, osmotic effects and fluid flow in morphogenesis (39)(40)(41)(42) and in previous models, osmolarity is most generally considered spatially homogeneous.…”
mentioning
confidence: 99%
“…The radius of curvature of a spherical interface is inversely proportional to the difference in pressure between the two sides of the interface. Thus, to analyse NC cytoplasmic pressure, we determined the radius of curvature of the posterior membrane of NCs, by measuring -in 2D optical sections-the radius of the circle fitting this membrane, as described in (Lamire et al, 2020), Figure S8A, B, E, n>12 per position). In agreement with previous results (Lamire et al, 2020), we found a gradient of cytoplasmic pressure decreasing from anterior to posterior in early S9 control egg chambers (Figure S8E).…”
Section: Bm Stiffness Influences Nc Cortical Tensionmentioning
confidence: 99%